Leadership Patterns and Social Capital in Rural Tourism: Lessons from Yogyakarta, Indonesia - Popi Irawan (Sasdaya: Gadjah Mada Journal of Humanities, 2025)
This study attempts to trace and uncover the roles and pattern of leaders and leadership in managing rural tourism attractions, which, in practice, are in forms of villages purposefully designed as destinations for tourists. Using social capital approach as a theoretical framework, this research attempts to place rural tourism leadership withing broader and complex social dynamics of rural society. Social capital is considered a useful framework to understand the complexity of rural society’s interaction and dynamics, including when rural tourism is introduced. The findings reveal that rural tourism leadership plays a pivotal role in advancing and maintaining the daily operationalization of tourism service provisions by communities. A leader of a so-called tourism village usually has to hold distinct social, educational, and cultural characteristics distinguishing her/him from the rest of the village communities. Due to this nature, local leadership exhibits elitism, where healthy community development process is at risk. Paradoxically, the concept of developing rural community-based tourism does not automatically result in shared/community-based leadership. Furthermore, to support leadership in the rural tourism setting, this study concurs with the literature suggesting that social capital is pivotal in maintaining and supporting the sustained practice of rural tourism. Therefore, managing a peculiar rural tourism attraction depends, to some extent, upon social capital properties.